Highly Skilled Italians’ Experience with Erasmus Mobility : Opportunities vs. Challenges - Samuk, Sahizer; Burchi, Sandra (Journal of International Students, 2023)
How does participation in the Erasmus program affect the future mobility and emigration decisions of highly skilled Italians? After conducting 51 semistructured and in-depth online interviews with highly skilled, spatially mobile, emigrant Italians, we used Atlas.ti to analyze each phrase, word, and context in which “Erasmus” appeared. More than two thirds of the interviewees had experienced the program, a substantial number of whom wanted to work in international environments and achieved their goals. A few returned to the city or country of their first Erasmus mobility experience. We argue that the mobility component of the Erasmus program provided the confidence required to be independent and the insight needed to make international comparisons. It also perpetuates the desire to travel abroad (to become spatially mobile) as participants sought additional international environments after the first Erasmus mobility experience, gaining additional self-confidence as a result.